A novel approach for one-sided thermal nondestructive testing of composites by using infrared thermography. (July 2015) - Vavilov, V.P.; Pawar, S.S.
Abstract: One-sided thermal non-destructive testing (TNDT) is of vital importance in aerospace composites to monitor structural degradation, as well as to detect subsurface defects. The objective of this study is to evaluate simultaneously the thermal diffusivity and to characterize the defects within carbon fiber reinforced polymer (CFRP) composites. In this paper, a novel one sided TNDT technique is presented which relies on creating an artificial inflection point by multiplying front-surface temperature evolution by n th power of time, where 0 <  n  < 0.5, followed by optimization of n . An analytical solution of the diffusivity calculation and defect characterization in the case of CFRP composite plate is discussed. The characterization of low velocity impact damage is also investigated with the help of theoretical and experimental results. Some key research points which need further exploration are also discussed.